Penerapan Model Pembelajaran Kooperatif Tipe Make A Match pada Materi Ikatan Kimia pada Siswa Kelas X SMA Negeri 3 Palu - Usia, Mirdawati; Tiwow, Vanny M. A.; Sabang, Sri Mulyani (Universitas Tadulako, 2018)
This study aimed to determine differences the learning outcomes of students in class using the cooperative learning model type make a match with class using conventional in the chemical bonding material in class X SMA Negeri 3 Palu. Type of research was a quasi-experimental design with non randomized pretest-posttest control group design. This research was carried out in two class of class X MIA 6 as an experimental group (n = 32) and class X MIA 7 as a control group (n = 30). Testing of learning outcomes of students data used t-test statistical analysis of the two parties with the prerequisite test: test for normality and homogeneity of a written test given after learning (posttest). The results of the data analysis, the average values obtained of class experiment (X1) was 69.00 with a standard deviation 10.66 and control class (X2) was 64.73 with a standard deviation was 11.38. Results of hypothesis testing, obtained that tcalct = 2.14 and ttable = 2.00 with a= 0.05 and degrees of freedom of 60. Results of the calculation the express that H0 was rejected and Ha was accepted. Based on the results obtained, it can be concluded that there were differences between the learning outcomes of students in chemistry class that using cooperative learning model type make a match, with the class using conventional on chemical bonding material in class X SMA Negeri 3 Palu.